Reticulospinal Systems for Tuning Motor Commands - Brownstone, Robert M.; Chopek, Jeremy W. (Frontiers in Neural Circuits, 2018)
The pontomedullary reticular formation is a key site responsible for integrating descending instructions to execute particular movements. The indiscrete nature of this region has led not only to some inconsistencies in nomenclature, but also to difficulties in understanding its role in the control of movement. In this review, we first discuss nomenclature of the reticular formation, and then examine the reticulospinal motor command system through evolution. These command neurons have direct monosynaptic connections with spinal interneurons and motoneurons. We next review their roles in postural adjustments, walking, and sleep atonia, discussing their roles in movement activation or inhibition. We propose that knowledge of the internal organization of the reticular formation is necessary to understand how the nervous system tunes motor commands, and that this knowledge will underlie strategies for motor functional recovery following neurological injuries or diseases.